Investigating hotel management system employed by SME business owner in rural area: a preliminary study - Abdul Rahman, Khadijah; Osman, Mohd Akmal Faiz; Mohd Ghazali, Siti Aswani; Hamidon, Huda; Abdullah, Nurulannisa (Faculty of Information Management, 2025)
The hotel industry extensively uses online automated systems to manage and enhance its operations, such as client reservations and payments, staff salaries and duties, pricing and refunds, marketing, and hotel review. The benefits of deploying hotel management systems has been well documented in the literature, however, these systems are typically used by well-established hotels that have the necessary resources and manpower. It is important to note that, in rural areas, there also exists a small business owner who runs and manages a hotel to serve the needs of its community with diverse capabilities in terms of resources, manpower and technological limitations. Thus, a preliminary study has been conducted by interviewing the business owner, staff, and their clients to investigate the hotel management system employed. The thematic analysis has shown that the limited capabilities have forced them to employ a manual system to manage their hotel. Issues and problems were found such as booking efficiency, customer support and satisfaction, financial transactions.